Physical properties of different thicknesses ZnO thin films prepared via sol-gel spin coating technique / Rohanieza Abdul Rahman ... [et al.] - Abdul Rahman, Rohanieza; Zulkefle, Muhammad Al Hadi; Herman, Sukreen Hana; Alip, Rosalena Irma (Universiti Teknologi MARA, 2021)
This paper presents the investigation of the thickness of the ZnO thin films by varying the number of deposition layers during the spin coating deposition process. ZnO thin films were deposited with a different number of layers (ranging from 1, 3, and 5), and the main purpose of this study is to explore the effect of the thickness on the properties of ZnO thin films. The deposited thin films were characterised using field emission scanning electron microscope, surface profilometer, and X-ray diffraction. From the characterisation results, the morphology of the ZnO thin films changed significantly with the number of layers and their thickness value. As expected, the thickness increased as the number of layers increased. The crystalline quality of the deposited film improved as the thickness increased. A change in crystallographic orientation was also observed in which the thicker, thin films showed crystal growth in the (102) direction, whereas the thinner one was in the (101) direction. A slight increase in crystallite size for dominant orientation also was observed with the increase of film thickness